WATER CHLORINATION AND ITS RELEVANCE TO HUMAN HEALTH - Botlagunta, Mahendran; JS, BONDILI; Mathi, Pardhasaradhi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Climatic conditions are fundamental to life on earth and their destruction or disturbance by direct or indirect human activities is the greatest threat to human health. Human life on earth is directly associated with environmental factors such as airâ€ and water.â€ Pollution of air by toxic substances by the activities of mankind has shown to cause serious health issues, including damage to the immune, respiratory, neurological, and reproductive systems, and other health problems like cancer. Water intended for human consumption should be free from microorganisms and toxic substances. The impact and drastic effects of chlorinated water and their impact on human health are poorly studied. Chlorination is an inexpensive and effective process for disinfecting water worldwide. During the disinfection, the chlorine generates hundreds of different by-products called chlorination by-products such as trihalomethanes and halo acetic acids (HAA's) at low levels. In this article we address the action of two HAA's, tri- and di-chloroacetic acid and their impact on the progression of cancer, respiratory disorder, and neurological anomalies. Keywords: Pollution, Chlorination, Chlorine by-products.